Egg Quality from Avian Species: Electrophoretic Characterization of Egg White Proteins - Meziani Samira; Drici Amine El-Mokhtar; Menadi Noureddine; Diaf Mustapha; Zairi Mohammed; Bouterfes Mohammed; Benali Mohammed (ANIMAL PRODUCTION, 2021)
The aim of the present study was to evaluate and to compare the physicochemical composition of egg white, and to characterize and estimate the quantitative variations of egg white proteins of different birds’ species (duck, quail, Chicken, partridge and goose). For each bird species, the whole egg temperature, weight, height, density and shape index were evaluated. After breaking the eggs, a visual examination was performed then vitelline (VI) and albumen (AI) indexes and the haugh unit (HU) were measured. The study of the quality and the characterization of egg white proteins were performed by Agarose Gel Electrophoresis. The total egg weight varied within a range of (8.98±0.82 g to 142.91±10.34 g) for quail and goose, respectively. The thickness of the egg yolk was almost three times higher than that of the egg white in all breeds. The egg freshness, measured by HU, was higher in partridge, followed by quail and chicken breeds with values of 88.81±0.09, 87.45±3.33, 81.53±2.16, respectively. The VI shows values of about 0.40. The egg yolk/ white ratio ranged from 47 and the pH varied from 8.37 to 8.95 for all local species studied. The egg white protein content was higher for all species (up to 14.45g/100 g). Three types of proteins are identified by agarose gel electrophoresis (ovalhibitor, ovotransferrin and ovalbumin) with a quantitative difference between bird species. Densitometric analysis shows a qualitative difference due to the presence of type C lysozyme in chicken egg white.